Corps singuliers et corps collectif - Laurent Gabail (Ateliers d'Anthropologie)
Unlike other comparable ritual traditions, the transformation implied by the performance of the Bassari’s male initiation ritual is not made visible by lasting marks on the initiates’ bodies (tattooing, scarifications, etc.). However, initiated men are periodically involved in group activities that cause their body to appear in a new light. The article examines two choreographic systems by means of which the effectiveness of the ritual is made visible to the public: group dances by men of the same age set, and masked performances. In the former case, the aim is to emphasise the equivalence that men of the same age set enjoy in principle, by attenuating, as much as possible, the corporeal differences that make each of them a unique person; in the latter case, the aim is conversely to emphasise an intrinsically individual corporeal quality of men partially anonymised by the costume of the mask: their voice.